TINJAUAN HUKUM TERHADAP MEKANISME PENGANGKATAN PEJABAT KEPALA DAERAH PENGGANTI KEPALA DAERAH YANG HABIS MASA JABATAN SEBELUM PEMILIHAN UMUM SERENTAK TAHUN 2024 - Intan Sri Anisa; Mahmuzar; Hellen Last Fitriani (ASAS Law Journal, 2023)
The background of this research is the appointment of acting regional heads to fill the vacancy of definitive regional head officials due to the postponement of regional elections in 271 regions in Indonesia which has caused problems in the administration of government in Indonesia. Therefore this study aims to find out how the legal review of the mechanism for appointing acting regional heads to replace regional heads whose term of office has expired before the simultaneous general elections in 2024, and to find out what impact the appointment of Acting regional heads carried out by the Ministry of Home Affairs has on the life of democracy and people's sovereignty . This research is a literature study and is a normative juridical law research that refers to legal norms. The type of data used is primary and secondary data. The data analysis technique applies qualitative research using a statutory approach and a conceptual approach by drawing conclusions using the deductive method. The results of this study are that the appointment of acting regional heads is not in accordance with the MKRI Decision Number 67/PUU XIX/2021 and the MKRI Decision Number 15/PUU-XX/2022 because it ignores the mandate of the decision in the form of establishing implementing regulations Article 201 UU 10/2016 and prohibiting the TNI and The National Police are active as acting officers. Basically the decision of the Constitutional Court is the final and binding decision. The authority of the Constitutional Court in examining laws against the 1945 Constitution places and becomes evidence for the Constitutional Court as a negative legislator. The appointment of acting regional heads is not in accordance with the principles of democracy because of the weak legitimacy of the local community, the weak supervision and control of the DPRD and the community as the holder of sovereignty, and the absence of accountability to the DPRD and the regional community.